Induction of Potent and Durable Neutralizing Antibodies Against SARS-CoV-2 Using a Receptor Binding Domain-Based Immunogen - Srivastava, Vikram; Niu, Ling; Phadke, Kruttika S.; Bellaire, Bryan H.; Cho, Michael W. (Frontiers in Immunology, 2021)
A novel betacoronavirus (SARS-CoV-2) that causes severe pneumonia emerged through zoonosis in late 2019. The disease, referred to as COVID-19, has an alarming mortality rate and it is having a devastating effect on the global economy and public health systems. A safe, effective vaccine is urgently needed to halt this pandemic. In this study, immunogenicity of the receptor binding domain (RBD) of spike (S) glycoprotein was examined in mice. Animals were immunized with recombinant RBD antigen intraperitoneally using three different adjuvants (Zn-chitosan, Alhydrogel and Adju-Phos), and antibody responses were followed for over five months. Results showed that potent neutralizing antibodies (nAbs) can be induced with 70% neutralization titer (NT70) of ~14,580 against live, infectious viruses. Although antigen-binding antibody titers decreased gradually over time, sufficiently protective levels of nAbs persisted (NT80 >2,430) over the five-month observation period. Results also showed that adjuvants have profound effects on kinetics of nAb induction, total antibody titers, antibody avidity, antibody longevity and B-cell epitopes targeted by the immune system. In conclusion, a recombinant subunit protein immunogen based on the RBD is a highly promising vaccine candidate. Continued evaluation of RBD immunogenicity using different adjuvants and vaccine regimens could further improve vaccine efficacy.